Can the International Index of Erectile Function (IIEF-5) be used as a diagnostic tool to the severity of vasculogenic erectile dysfunction? - Elnashar, Abdelrahman; Gadallah, Amr M.; Abdelaal, Alaa A.; Soliman, Islam F.; Youssef, Mohamed A.F.M. (Middle East Fertility Society journal, 2012)
The objective of this observational study was to compare the International Index of Erectile Function (IIEF-5) with penile duplex in the diagnosis of vasculogenic erectile dysfunction severity. 150 subjects complaining of erectile dysfunction for >6months have been divided into two groups according to their response to intracavernous injection (ICI) test; 50 patients who showed good response⩾(E4) and one hundred patients who showed poor response⩽(E4) up to maximum dose of 1cc Quadmix with abnormal penile duplex. The results of the duplex are correlated to the IIEF-5 score of the patients. There is statistically significant difference between mean value of IIEF-5 in both good and poor responders (P-value=0.0000), significant difference between mean value of (age, duration, PSV, EDV, diameter of artery after injection, percent of increase in arterial diameters and RI) between the good and poor responders. There was no evidence of statistically significant difference between mean value of IIEF-5 in both arteriogenic and venogenic subgroups of poor responders group. There was neither evidence of statistically significant correlations between IIEF-5 and penile duplex results in both good and poor responders groups, nor between IIEF-5 and penile duplex results in arteriogenic and venogenic and combined subgroups. IIEF-5 might not be a suitable diagnostic tool of the severity of vascular affection in ED.